Association between an oncology psychology course and caring ability improvements in postgraduate medical students - Hua, Xin; Xiao, Lin; Wu, Lu; Chen, Jie-Wen; Du, Sha-Sha; Xie, De-Huan; Sun, Heng-Wen (Frontiers in Psychology, 2025)
BackgroundCancer patients experience significant psychological distress that requires healthcare providers with well-developed caring abilities. Medical education traditionally underemphasizes humanistic competencies, particularly in oncology contexts. This study aimed to evaluate the impact of a specialized oncology psychology course on the caring ability of postgraduate medical students specializing in clinical medicine.MethodsA quasi-experimental pre-post design was used with a sample of 32 postgraduate medical students who completed both pre- and post-course assessments. The study was conducted at South China University of Technology in Guangzhou, from September 2024 to January 2025. The oncology psychology course incorporating theoretical foundations, psychological assessment, intervention strategies, and clinical applications through multimodal pedagogy including lectures, case discussions, standardized patient simulations, and clinical observations. The Caring Ability Inventory (CAI) was used to measure caring ability across three dimensions (Knowing, Courage, and Patience) before and after the course. Paired t-tests and independent samples t-tests were employed to analyze data using SPSS version 23.0.ResultsA total of 32 students completed both assessments. The total CAI score increased significantly from pre-course to post-course (188.53 ± 20.74 vs. 197.53 ± 22.75, P < 0.001). Significant improvements were observed in all three dimensions: Knowing (71.72 ± 8.95 vs. 75.97 ± 10.15, P < 0.001), Courage (57.69 ± 10.50 vs. 60.31 ± 10.71, P < 0.001), and Patience (59.13 ± 5.34 vs. 61.30 ± 5.47, P < 0.001). Female students demonstrated consistently higher Patience dimension scores than males both before and after the course (P < 0.05). Student leaders showed superior total CAI and Courage dimension scores compared to non-leaders at both time points (P < 0.05).ConclusionsThe oncology psychology course was associated with significant improvements in caring ability among postgraduate medical students across all dimensions. The findings support the integration of specialized psycho-oncology curricula in medical education and highlight the importance of considering demographic factors in educational design. This evidence-based approach to developing caring competencies addresses critical gaps in preparing future oncologists for patient-centered care.